French wine : a history - Phillips, Roderick (University of California Press, 2016)
"A survey of the long-term history of wine in France, this is a readable and relatively compact history of the 2,500 years that separate the present from the time that Etruscans, Greeks, and Romans first brought to ancient France and planted the first vineyards there. The book traces this long history at a number of levels: the expansion and contraction of regional and national vineyard areas; long- and short-term changes in the volumes of wine produced; the effects of long- and short-term climate shifts on viticulture and wine production; the emergence of recognizable wine regions and designated appellations; changing methods of viticulture and winemaking; the marketing of wine locally and regionally within France and internationally; the reception of wine on domestic and foreign markets; the diverging levels of quality and the emergence of prestigious wine regions and estates; the evolving definition of terroir; the regulation of wine production and sales and the prevention of fraud; patterns of wine consumption in France; and the relationship of wine to gender, class, health, religion, and identity in France."--Provided by publisher